organized student group contributions “amautasminga” in environmental education (Revista Electrónica REDINE, 2018)
This work is framed in a quantitative research, based on a study of descriptive field, in order to analyze the contribution of organized group student Amautasminga Program Higher Agricultural Technology at UCLA, in promoting environmental education in the Carora community of the municipality Towers. The study subjects were represented by thirty-five students belonging to Amautasminga group who were administered a standard questionnaire instrument structured for forty items each with three alternative answers: always (S) Sometimes (AV) and Never (N). This instrument was validated through expert judgment and statistical reliability was used Cronbach alpha coefficient, obtaining a value of 0.94. The results were analyzed according to the criteria of descriptive statistics, estimating absolute and percentage frequencies and the simple average for response options, which reflects that the majority of students in the group expressed own environmental sensitivity and high concern for developing  projects with focus Environmental contributing to preserving the environment, also active in the promotion of environmental education to help environmental conservation and integrate Carora communities in solving social and environmental problems in the environment where they make active life.
Keywords: organized student groups; environmental education; questionnaire